Motivation to Follow a Career in Dentistry of Students in Three South-East European Countries - Julijana Nikolovska; Kenneth A. Eaton; Nikolina Kenig; Dorjan Hysi; Nilkola Petričević (University of Zagreb. School of Dental Medicine, 2020)
Objective: To investigate and compare the factors that motivated students to study dentistry in countries with similar background (Albania, Croatia and the Republic of Northern Macedonia) and to as-sess whether or not their motivation changed during time. Material and methods: In 2014/2015,cross-sectional studies were conducted in state funded dental schools in Tirana (Albania), Zagreb(Croatia) and Skopje (North Macedonia) to assess student views on their career motivation. All den-tal students from the first, third and final years of study were invited to participate. The participationwas voluntary and anonymous. A five-item questionnaire was translated into languages of the par-ticipating countries. Ethics approval was granted by the Ethics Committee of the University of SaintsCyril and Methodius, Skopje. The Chi square test was used to test if there were statistically significantdifferences in answers between students in 3 countries, furthermore between years of the study.Re-sults: The total number of respondents was 739 (319 in Tirana, 211 in Zagreb and 208 in Skopje) Thedifferences in the answers between the first-year students from all three countries were statistical-ly significant (χ2=82.65; p<.01). The most striking answer was to the question on parents' pressureto study dentistry, which was far more frequent in Tirana (up to 27.7%). A "positive image" was themost frequent response from students from Zagreb (up to 79.7%), but it declined from the first to thefinal year in Skopje. There were also significant differences the schools within the 3rdand final years of study. Conclusions: A positive image of dental profession was the main reason for students studying dentistry at all three schools; as many as 97% of the students of the final year in Croa-tia, a member of the European Union (EU). In the two non-EU countries (Albania, North Macedonia) itseemed that dental profession does not have such good status and student expectations are not be-ing fulfilled, especially in Skopje (up to 33.9% willing to change their vocation and up to 64.5% losttheir motivation to study) One of the strategies to improve the situation could be to include more clinical practice and to better organize the study.